2018
DOI: 10.3390/ijerph15061086
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Lead Exposure and Adult Literacy in Myanmar: An Exploratory Study of Potential Associations at the Township Level

Abstract: Environmental lead exposure is a population health concern in many low- and middle-income countries. Lead is found throughout Myanmar and prior to the 1940s the country was the largest producer of lead worldwide. The aim of this study was to examine any potential association between lead mining and adult literacy rates at the level of 330 townships in Myanmar. Townships were identified as lead or non-lead mining areas and 2015 census data were examined with association being identified using descriptive, analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…One study also examined adult literacy across Myanmar and found lower levels of literacy in townships with lead mining activities, even amongst those with access to high-quality sanitation infrastructure, which may indicate wider environmental exposure to mining by-products [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study also examined adult literacy across Myanmar and found lower levels of literacy in townships with lead mining activities, even amongst those with access to high-quality sanitation infrastructure, which may indicate wider environmental exposure to mining by-products [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study also examined adult literacy across Myanmar and found lower levels of literacy in townships with lead mining activities, even amongst those with access to high-quality sanitation infrastructure, which may indicate wider environmental exposure to mining by-products [51].…”
Section: Heavy Metalsmentioning
confidence: 99%
“…In turn this could significantly alter the mobilization of trace elements in these river catchments, with negative consequences for water quality. Land disturbance by mining activities has increased in these catchments in recent decades (LaJeunesse et al, 2016;Bhagwat et al, 2017) and there is already concern over water quality in parts of these river catchments due to mining related trace element pollution (MacTavish et al, 2018, Kawakami et al, 2019, Kyaw Zay Ya et al, 2020, Shrestha et al, 2020. A lack of data in these river catchments however currently hinders a rigorous assessment of such concerns.…”
Section: Introductionmentioning
confidence: 99%